Career Preparation Program Model at The Sub Directorate of Career Development and Assessment (CDA) IPB University - Rici Tri Harpin Pranata; Nur Fajri Rahmawati (Batrisya Education, 2024)
Changes in the job map provide career challenges for college graduates. On the other hand, the Ministry of Education, Culture, Research, and Technology makes higher education performance assessments through the IKU PTN to see the absorption of graduates. This research uses quantitative data from the 2018-2023 annual CDA report. Analysis of research data using the SWOT method. Data is presented descriptively to obtain an overview of the implementation of student career preparation programs. For 5 years, CDA IPB has held various career preparation programs, namely membership services, career service information system, on-campus recruitment & publication of job vacancy information, career training & industrial insight, career consultation, job fair, career enrichment, career buddy, stadium general for graduation, internship, career faculties roadshow, career studio, and career preparation in multinational companies. Based on the results of the analysis carried out using the SWOT method, it can be concluded that the CDA programs have been running effectively with several parameters increasing the number of program users, the distribution of work status, as well as testimonials from graduates who have participated in the CDA programs.